KONTRIBUSI EQUITAS MEREK DAN PENINGKATAN KUALITAS PELAYANAN DALAM MEMAKSIMALKAN TINGKAT KEPUASAN PELANGGAN UNTUK MOTOR HONDA BEAT PADA PT SELAMAT LESTARI MANDIRI SUKABUMI: Manajemen pemasaran - REKA ARDIAN PURNAMA (Ekonomedia, 2021)
Contribution to improving the quality of the brand is an important factor in determining the product. Only in this way can the level of consumer satisfaction be maintained in the brand's brand equity, which automatically brings the level of consumer satisfaction with the brand's products to the level. As one of the Brands sold by PT Selamat Lestari Mandiri Sukabumi, as one of the high quality products, consumers like the Honda Beat brand, which is a very popular motorcycle brand. However, the competition in the field of motorcycle sales is very fierce. Therefore, needs, which is the precise strategic method of and can maintain levels of customer satisfaction. Uses methods to increase the brand equity of Honda Beat. The research method used in this study is a descriptive method, with objectives, capable of observing and explaining descriptions of each independent variable listed in this study. The survey method was used for data collection purposes. The results show that brand equity quality and service improvement have a significant impact on customer satisfaction